Characterization of Solar Energetic Particle Radiation Dose to Astronaut Crew on Deep‐Space Exploration Missions. Issue 12 (5th December 2019) - Mertens, Christopher J.; Slaba, Tony C.
Abstract: Human radiation exposure from solar energetic particle (SEP) events during deep‐space exploration missions has a greater impact on mission planning and operations compared to spaceflight missions to low Earth orbit. Deep‐space SEP radiation exposure may require in‐flight preventative actions in order to reduce the radiation risks to as low as reasonably achievable, to limit the onset and severity of acute biological responses, and to ensure that astronaut permissible exposure limits are not exceeded. In this paper, radiation dose to the blood forming organs (BFO) of astronaut crew is calculated from a set of historical SEP events, using the design of the Orion Multipurpose Crew Vehicle (MPCV). The BFO doses from the historical events are analyzed in several ways. The results show the range and upper limit of BFO doses expected in heavily shielded space vehicles such as the Orion MPCV, based on calculations from all the major SEP events encountered in the space age. The dose reduction properties of the MPCV storm shelter are characterized over the broad range of SEP events included in the historical database. Correlations are derived between the integral proton fluence and BFO dose in the vehicle, showing that integral fluence is a good proxy for predicting or forecasting vehicle BFO dose. The best correlation with MPCV BFO dose is from the >100 MeV integral fluence. These results will assist in the design of future space weather architectures by identifying models and measurements needed to expand and extend NASA's existing SEP radiation risk tools in the support and management of human space exploration missions. Key Points: Heavily shielded spacecraft can limit acute biological responses to worst‐case SEP events Integral proton fluence is a good proxy for vehicle dose during SEP events Vehicle storm shelters can reduce SEP dose by 38% on average and factor two for soft events